2022
DOI: 10.3390/jof8050433
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield of Purple Kculli Corn Plants under Different Fertilization Schemes

Abstract: Globally, corn is the most economically important crop, surpassing other cereals of economic importance. However, the tillage methods, monoculture and the abuse of synthetic agrochemicals used in Mexico have led to the loss of fertility and soil yield. In this sense, the application of alternative fertilization methods based on chemical fertilizer, organic matter and biofertilizer, applied alone or in combination, can stimulate the defense systems of corn plants and increase their yield. Therefore, in this res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…These results are similar to the percentages of 0.81 and 0.83 ears per plant obtained in treatments T2 and T3, during the year 2019. In this regard, periods of atypical rainfall during key stages of the crop can cause the abortion of grains and ears, giving rise to ear percentages below one unit (Romero-Cortes et al, 2022b). In other studies, with Chalqueño maize was reported that they can obtain from 0.9 to 1.1 ears per plant, under very favorable experimental and rainfed conditions (Arellano et al, 2003;Velázquez, 2013).…”
Section: Ear Per Plantmentioning
confidence: 98%
See 3 more Smart Citations
“…These results are similar to the percentages of 0.81 and 0.83 ears per plant obtained in treatments T2 and T3, during the year 2019. In this regard, periods of atypical rainfall during key stages of the crop can cause the abortion of grains and ears, giving rise to ear percentages below one unit (Romero-Cortes et al, 2022b). In other studies, with Chalqueño maize was reported that they can obtain from 0.9 to 1.1 ears per plant, under very favorable experimental and rainfed conditions (Arellano et al, 2003;Velázquez, 2013).…”
Section: Ear Per Plantmentioning
confidence: 98%
“…The harvest of the ears was carried out once the crop reached its physiological maturity between the first and second week of October of the years 2019 and 2020, respectively. At the end of the crop cycle, the following agronomic characters were recorded: plant height, stem diameter, ear length and diameter (cm), ears per plant and grain yield adjusted to 12% H2O, using the conversion factor of the harvested area with respect to one hectare, expressed in t ha -1 (Romero- Cortes et al, 2022b).…”
Section: Treatments and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Te plant height and diameter of glutinous corn were collected by measuring from the soil surface to the apex of the spike in centimeters, and the diameter of the plant was measured at 5 cm above the ground at 20 DAS and harvest [12]. Te number of leaves was counted per plant at 20 DAS and harvest.…”
Section: Monitoring Parametersmentioning
confidence: 99%